THE INFLUENCE OF DIVIDEND POLICY TO THE COMPANY'S STOCK PRICE INCORPORATED IN LQ45 INDEX LISTED ON INDONESIA STOCK EXCHANGE (IDX) IN THE YEAR OF 2009-2013 - B12111004, Juviyanti (Jurnal Manajemen Update, 2015)
This research was conducted to examine the influence of dividend policy to the company's stock price incorporated in LQ45 Index. The benchmark of the dividend policy are Dividend per Share (DPS) and Dividend Payout Ratio (DPR). In addition, it also considered Free Cash Flow (FCF) and Market-to-Book Equity Ratio (MVEBVE) as the control variables. Population of this research is 45 companies incorporated in the index listed on Indonesia Stock Exchange (IDX) in the year 2009-2013 and by purposive sampling the sample size is 15 companies. The data was collected through literature review and documentary studies. The analysis technique used was panel data and multiple regressions analysis. The research found that DPS has positive and significant influence on the stock price; DPR and FCF has negative and insignificant influence toward the stock price; and Market-to-Book Equity Ratio (MVEBVE) has positive and significant influence toward the stock price. Keywords: Stock Price, Dividend Policy, Dividend Per Share (DPS), Dividend Payout Ratio (DPR), Free Cash Flow (FCF), Market-to-Book Equity Ratio (MVEBVE)